Sistem Perpajakan Dalam Perspektif Al-Mawardi - Hamzah, Ali (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2007)
This article describes al-Mawardis thoughts ontaxation (kharaj). This library research employs content analytical approach in its data analysis and adopts the axiom that the study of process and the content of community constitute the basis for all science. Mewardi is in the opinion that the government has the authority to collect and raise fund for the interest and benefit of the people in whole in theform of pungutan wajib (cornpulsory contribution) like taxes and zakat (obligatory alms-giving), The amount to be paid should be progressive in their implementation (Thxes and zakat). The writer hopes that the readersawareness is increase to pay their taxes and zakat after reading this article.